Student Engagement, 'Learnification' and the Sociomaterial: Critical Perspectives on Higher Education Policy. Issue 1 (March 2017) - Gourlay, Lesley
Abstract The term 'student engagement' has become ubiquitous in mainstream discourses concerning higher education in the UK and beyond. The term is used to denote a desirable set of practices and orientations in students which should be worked towards or encouraged in order for teaching in higher education to be deemed successful — as such, it has enormous influence in the higher education (HE) as part of a discourse which carries powerful ideological force in the sector. However, as Kahn (Br Educ Res J 40(6):1005–1018, 2013) points out, it is a concept which is weakly theorised in the literature. This paper will interrogate the concept in order to deepen understanding of how the term operates. I will argue first that the notion often relies on typological categories which tend to posit the individual as the primary site of student engagement and secondly that this is primarily identified in interlocution or observable interaction. Drawing on the work of Gert Biesta, I will argue that this position reflects a broader trend towards 'learnification' in higher education, which positions teaching as problematic and inherently repressive. I seek to build on this critique by arguing for a reframing which recognises the sociomaterial and radically distributed nature of human and non-human agency in day-to-day student engagement.